2003
DOI: 10.1002/cvde.200390000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Added Iodine Source (C2H5I) on Ru Metal–Organic Chemical Vapor Deposition

Abstract: The effects of an iodine source (C 2 H 5 I) on ruthenium (Ru) films grown on TiN/Ti/Si wafers by metal±organic (MO)CVD using Ru(EtCp) 2 as a precursor were investigated. When an additional step of adsorbing iodine source was inserted during the Ru MOCVD process, the films became smoother and the root mean square (rms) surface roughness of the 30 nm thick Ru film became less than 10 % of the film thickness, as low as 1.71 nm. Moreover, the surface reaction-limited regime was extended to 400 C, causing a wide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Before the TPR, the ratio is 2.6, in good agreement with the literature value for carbon-free Ru. [8,22] After the TPR, the ratio increases to 3.1 indicating that C is co-deposited.…”
Section: Reaction On Al 2 O 3 Partially Covered With Rumentioning
confidence: 93%
See 1 more Smart Citation
“…Before the TPR, the ratio is 2.6, in good agreement with the literature value for carbon-free Ru. [8,22] After the TPR, the ratio increases to 3.1 indicating that C is co-deposited.…”
Section: Reaction On Al 2 O 3 Partially Covered With Rumentioning
confidence: 93%
“…The sticking probabilities can be largely increased when surfaces were modified via adsorptions of CH 3 I or C 2 H 5 I, and smoother films were obtained. [7,8] Importantly, the characterization of different surface O states on a seed layer of Ru suggests that, in the film growth, the reaction rates are not just dependent on the substrate temperature, but on the population of the different surface oxygen states. In our experiments, the substrate was exposed to 5 10 ±4 torr of O 2 for 1 h prior to the reaction, and was presumably saturated with surface oxygen.…”
Section: Relevance To Practical Cvd Processesmentioning
confidence: 99%
“…These researchers expanded on the work of Hwang et al [17,18] who showed that during Cu CVD, iodine acted as a catalytic surfactant to reduce surface roughness, in a manner similar to 0039 surfactant addition in homo-and hetero-epitaxy. Kim et al also observed that iodine addition impacts CVD Ru films; adsorbed iodine results in smaller, denser nuclei, which leads to films with smaller grain size and improved film roughness [15,16]. Hwang et al have shown that the particular iodine source being used is not significant, as long as the iodine-containing molecule leaves only adsorbed iodine on the growing film surface.…”
Section: Introductionmentioning
confidence: 95%
“…One such attempt by Kim et al [15,16] involved the introduction of an iodine source (i.e., CH 3 I, C 2 H 5 I) during film growth. These researchers expanded on the work of Hwang et al [17,18] who showed that during Cu CVD, iodine acted as a catalytic surfactant to reduce surface roughness, in a manner similar to 0039 surfactant addition in homo-and hetero-epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The three statistical surface parameters of the GW model can be calculated following the method detailed in the previous section. The roughness of a Ru film under different deposit methods was measured by Kim et al [51], the initial tip radius R is the one studied in Section 2.2, and the asperity density N is a typical value for deposition. Ru films are deposited on the movable electrode, and also on a part of the substrate, and are characterized by a thickness t s and a Young modulus E s .…”
Section: Application To a 1d Micro-switchmentioning
confidence: 99%